2021
DOI: 10.1186/s13005-021-00264-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different surgical techniques and displacement distances on the soft tissue profile via orthodontic-orthognathic treatment of class II and class III malocclusions

Abstract: Background Orthognathic surgery can be carried out using isolated mandibular or maxillary movement and bimaxillary procedures. In cases of moderate skeletal malocclusion, camouflage treatment by premolar extraction is another treatment option. All these surgical procedures can have a different impact on the soft tissue profile. Methods The changes in the soft tissue profile of 187 patients (Class II: 53, Class III: 134) were investigated. The treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
6
0
2
Order By: Relevance
“…These findings were also reported in former investigations 29 31 . In this context, recently, Möhlhenrich et al investigated the effects of different surgical techniques and displacement distances on the soft tissue profile retrospectively 32 . They found that for the mandibular setback in class III patients, only a slight increase in nasolabial angle (up to 2.13° ± 4.78°) and distance Ls-E-Line (up to 1.69 ± 2.12 mm) occurred.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were also reported in former investigations 29 31 . In this context, recently, Möhlhenrich et al investigated the effects of different surgical techniques and displacement distances on the soft tissue profile retrospectively 32 . They found that for the mandibular setback in class III patients, only a slight increase in nasolabial angle (up to 2.13° ± 4.78°) and distance Ls-E-Line (up to 1.69 ± 2.12 mm) occurred.…”
Section: Discussionmentioning
confidence: 99%
“…La mejor manera de afrontar la maloclusión Clase II división 1 severa, es el tratamiento quirúrgico (Gumiela M. et al 2019) pero existe la alternativa de un camuflaje ortodóncico. (Möhlhenrich S. et al, 2021) En su estudio retrospectivo se centró en pacientes límite que claramente requerían cirugía ortognática sin una alternativa de tratamiento únicamente de ortodoncia. El objetivo era determinar la influencia de estos diferentes enfoques.…”
Section: Discussionunclassified
“…We found that soft tissue behavior differed between the maxillary advancements combined with mandibular setback or bimaxillary procedures, which were more equal to each other. 5 Thus, after some consideration, the Le Fort I osteotomy and mandibular bilateral sagittal split and anterior subapical osteotomies were chosen.…”
Section: Discussionmentioning
confidence: 99%